2000
DOI: 10.1379/1466-1268(2000)005<0291:tdohsp>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of heat shock proteins in the nervous system of the unstressed mouse embryo suggests a role in neuronal and non-neuronal differentiation

Abstract: Heat shock proteins (Hsps) act as molecular chaperones and are generally constitutively expressed in the absence of stress. Hsps are also inducible by a variety of stressors whose effects could be disastrous on the brain. It has been shown previously that Hsps are differentially expressed in glial and neuronal cells, as well as in the different structures of the brain. This differential expression has been related to specific functions distinct from their general chaperone function, such as intracellular trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 73 publications
2
60
0
3
Order By: Relevance
“…Tissue extracts (TE) and whole-cell extracts (WCE) from K562 cells were prepared as described by Mosser et al (1988) or Loones et al (2000). Approximately 20-36 µg of TE or WCE per sample was used for SDS-PAGE.…”
Section: Ip and Western Blot Analysismentioning
confidence: 99%
“…Tissue extracts (TE) and whole-cell extracts (WCE) from K562 cells were prepared as described by Mosser et al (1988) or Loones et al (2000). Approximately 20-36 µg of TE or WCE per sample was used for SDS-PAGE.…”
Section: Ip and Western Blot Analysismentioning
confidence: 99%
“…Studies involving experimental exposure to electromagnetic fields have revealed numerous modifications in the expression of heat shock proteins in vivo [8] and in vitro, in cell lines [9]. HSP-90 is the most common type of heat shock protein [10] and occurs at higher levels in nerve tissues than in non nerve tissues [11] and is distributed in neurons in the limbic system, neocortex, striatus and thalamus [12,13]. This protein acts to regulate the activity of other proteins such as steroid hormone receptors [14] kinase [15], calmodulin [16], actin [17], and tubulin [18].…”
Section: Introductionmentioning
confidence: 99%
“…3 ± 7 It appears to be highly expressed in specific organs or tissues such as the heart, 8 skeletal striated muscles, epidermis, cartilage, bone 9 and specific areas of the central nervous system. 10,11 But nothing is known about how the possible role of this protein may explain such a specific distribution.…”
Section: Introductionmentioning
confidence: 99%